Role Playing Game (RPG) on nursing undergraduate course: educational potentials - Amanda Nathale Soares; Maria Flávia Gazzinelli; Vânia de Souza; Lucas Henrique Lobato Araújo (Universidade Federal de Goias, 2016)
The objective of this study was to evaluate the potential of a Role Playing Game as an educational strategy in Undergraduate Nursing course, emphasizing its subjective implications in understanding aspects of the profession. This is a qualitative study, conducted through an evaluative research, of deployment analysis type. Nursing students of the 3rd period participated. The instrument to collection was Memories of Game, reports prepared by students after game sessions. The game is a non-traditional educational strategy that enabled approach to students through professional practice, active participation, self-reflection and reflection on professional practice. This strategy favored individualization processes, allowing students to experience situations similar to the nursing practice and exercise skills such as teamwork and creativity. The expansion of studies that address the subjective processes in higher education, through simulation games, can contribute to better design of health development processes.